Acyclovir-Induced Neurotoxicity: A Case Report and Review of Literature. (May 2016) - Chowdhury, Mohammed Andaleeb; Derar, Nada; Hasan, Syed; Hinch, Bryan; Ratnam, Shoba; Assaly, Ragheb
Abstract : Neurotoxicity can develop as a side effect of intravenous acyclovir use in patients with renal impairment. It is underreported in clinical practice and often confused with worsening herpes encephalitis. We present a 69-year-old woman with end-stage renal disease on hemodialysis with acyclovir neurotoxicity treated with daily extended hemodialysis sessions. Daily hemodialysis for extended period may shorten the neurotoxicity period and can help with faster return to normal mentation. A high index of suspicion is warranted to diagnose acyclovir-induced neurotoxicity.